Gods and Colonists from Asia Minor in Dacia - Ioan Piso (Gephyra, 2018)
The author is dealing with the divinities and colonists of the province Dacia who originated from Asia Minor, utilizing 66 known epigraphic documents and reinterpreting many of them. The divinities which had penetrated all the layers of the Roman society for a long time and those venerated exclusively by Microasiates are differenciated. To the first category belong Magna deum Mater, identified in most cases with Kybele, followed by Sabazios and Men. To the second category belong Adrastia, Iupiter Bussurigius, Iupiter Cernenus, Iupiter Cimistenus, Iupiter Erusenus, Iupiter Tavianus, Ζεὺς Ἑπτακωμικός, Ζεὺς Ναρηνός, Ζεὺς Σαρδενδηνός, Ζεὺς Σύργαστος, Μήτηρ Τροκλιμηνή. Doubtful cases are also mentioned. We notice the frequency of the cults coming from Galatia. As to the persons from Asia Minor, the soldiers came from almost all areas of the researched zone and got to Dacia according to their recruitment and to their career. As to the colonists, most of them were from Bithynia, Galatia and neighboring regions. They were engaged in trade and crafts and belonged to all the social layers.